Coastal waters contamination by mining tailings: What triggers the stability of iron in the dissolved and soluble fractions?. Issue 1 (28th September 2020) - Longhini, Cybelle Menolli; Mahieu, Léo; Sá, Fabian; van den Berg, Constant M. G.; Salaün, Pascal; Neto, Renato Rodrigues
Abstract: The solubility of iron (Fe) in seawater is greatly enhanced by complexation with organic ligands, predominantly occurring as humic substances (HS) in coastal areas. Mining exploitation is believed to change the natural biogeochemical cycle of Fe in coastal waters, even though its impacts on the physical and chemical speciation of the Fe fractions are not known. Here we show that dissolved and soluble Fe concentrations in coastal waters affected by a mining catastrophe (Fundão dam, Southeast Brazil) remain very high, even almost 3 years later, with concentrations of dissolved Fe up to 2.8 μ M (0.45  μ m filtration) or 700 nM (0.22  μ m filtration), and soluble Fe (0.02  μ m) up to 40 nM. Levels of humic substances can only explain the binding of 2% and 10% (median values) of dissolved Fe (0.22  μ m) and soluble Fe concentrations, respectively, which shows that processes other than complexation with humic substances are at play to maintain such high dissolved Fe concentrations. We hypothesize that the colloidal phase that dominates the dissolved Fe fraction occurs as Fe(III) oxyhydroxides while the soluble fraction is comprised of Fe(III) complexes with amine compounds (widely used in the ore extraction process). Mass balance of dissolved Fe in the water column suggests that sediment resuspension on the continental shelf is by far the dominant process delivering dissolved Fe to coastal and shelf waters. Estimates of dissolved Fe yearly fluxes highlight the sheer magnitude of this catastrophe that might provide a non‐negligible amount of dissolved Fe to the open ocean.